The Masters of Suspicion : The Wisdom of Supreme Masters - john christianto simon (Celebes Education Review, 2020)
Three masters of suspicion, i.e. Marx, Freud and Nietzsche, each spoke of a critical task in the realm of human action. Marx suspected that economic motives were often not to support life but instead to suppress it. Nietzsche suspected that religion only produced decadent and timid humans so they never became their true selves, hypocrites and like to scare others. Freud was suspicious of human subconscious motivation so that it must be seriously criticized in order to an action was truly born of compassionate political and social morality. These three masters present important pedagogic values ​​to be developed today, namely education for social change, education for empowerment and education to build a compassionate social and political morality.